2017
DOI: 10.1002/jor.23710
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between RUST assessments of fracture healing to structural and biomechanical properties

Abstract: Radiographic Union Score for Tibia (RUST) and modified RUST (mRUST) are radiographic tools for quantitatively evaluating fracture healing using a cortical scoring system. This tool has high intra-class correlation coefficients (ICCs); however, little evidence has evaluated the scores against the physical properties of bone healing. Closed, stabilized fractures were made in the femora of C3H/HeJ male mice (8-12 week-old) of two dietary groups: A control and a phosphate restricted diet group. Micro-computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
2
54
1
Order By: Relevance
“…This study also suggests some potential difficulties with the widely used RUST score. Our RUST scores intra-class correlation coefficient (ICC = 0.727) was comparable to the RUST repeatability recently reported by many other investigators, 9,10,22,23,28,29 but was not as good as the original reports. 8 Notably, none of these reports show that RUST scoring meets the strictest definition of ICC>0.9 for an assessment to be deemed "reasonable for clinical measurements", 30 even in studies using simple transverse osteotomies in animal models.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study also suggests some potential difficulties with the widely used RUST score. Our RUST scores intra-class correlation coefficient (ICC = 0.727) was comparable to the RUST repeatability recently reported by many other investigators, 9,10,22,23,28,29 but was not as good as the original reports. 8 Notably, none of these reports show that RUST scoring meets the strictest definition of ICC>0.9 for an assessment to be deemed "reasonable for clinical measurements", 30 even in studies using simple transverse osteotomies in animal models.…”
Section: Discussionsupporting
confidence: 89%
“…8 Notably, none of these reports show that RUST scoring meets the strictest definition of ICC>0.9 for an assessment to be deemed "reasonable for clinical measurements", 30 even in studies using simple transverse osteotomies in animal models. 22,23 Furthermore, our data indicates that RUST scores may not have prognostic validity for predicting longitudinal outcomes, an issue that was raised early in the history of the RUST scoring, 31 but has been neglected in favor of repeated examination of inter-and intra-rater reliability. Interpreted cautiously, our data supports the general conclusion that RUST is useful for differentiating between healed and unhealed fractures, but may be lacking in sensitivity and specificity as a surrogate measure of callus structural integrity, particularly in early healing (non-united RUST < 10).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…( 31 ) The formation of calluses and the visibility of fracture lines on radiographs of femora were observed. Afterwards, the RUST score, ( 16 ) which has been proved to be a reliable and valid strategy to assess fracture healing in both clinical and animal studies, ( 32,33 ) was used to provide a way for quantification and statistical analysis. Our results showed that CS 129X1/SvJ mice exhibited less callus formation and visible fracture lines, while other groups showed robust healing.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic surgeons rely on subjective physical examinations, clinical experience, and radiographic techniques to visually assess the development of mineralized tissue in order to diagnose healing progression. [5][6][7][8] Delayed healing and non-union are clinical diagnoses based on symptoms of pain, instability, and poor radiographic bone healing at a time point after which healing should be expected. Criteria that define delayed union and non-union in clinical settings are variable, and there remains no single consensus definition.…”
Section: Introductionmentioning
confidence: 99%